MODEL BERWIRAUSAHA TERHADAP PRESTASI MATEMATIKA MAHASISWA UNIVERSITAS TRIBUANA KALABAHI - Maktisen Ena; Narita Y. Adrianingsih; Falentina L. Kamutlaka (LPPM Universitas Bina Bangsa, 2023)
This research aims to determine whether there is an influence between entrepreneurship on student achievement, in this case student learning achievement and to find out how to analyze it. The population in this study were all Tribuana Kalabahi University students, totaling 3,101 students. In this research, 153 students were taken randomly (when the students met, the researchers immediately asked questions) at Tribuana Kalabahi University. The method used in this research is an interview, namely randomly interviewing students at Tribuana Kalabahi University. Then the data obtained from the interview results was processed through the SPSS program application with a simple linear regression statistical analysis tool. Judging from the significance value or p-value of 0.008, which is smaller than alpha 0.1, it can be concluded that entrepreneurship has a significant effect on student learning achievement. The regression equation model is Y=3.518-0.093x, because the coefficient value is minus (-) meaning that entrepreneurship (X) has a negative effect on the student's Learning Achievement Index (Y). Which means that if x has a value of 0 or is said to be non-entrepreneurial then the student's cumulative achievement index is 3.518. Meanwhile, if x has a value of 1 or is said to be entrepreneurial, the student's cumulative achievement index will decrease by 0.093. So it can be said that if students have entrepreneurship while studying, the cumulative achievement index will decrease. From the results of the coefficient of determination test, it was found that the independent variable number, namely entrepreneurship, was 4.5%, which could explain/explain the dependent variable, namely achievement, or in other words, entrepreneurship influenced student achievement by 4.5%, while the remaining 95.5% was explained/explained by other factors. which was not researched